Tinjauan TINJAUAN LITERATUR: DINAMIKA REGULASI EMOSI, RESILIENSI, DAN FENOMENA NSSI REMAJA - Moh. Andre Sahputra; Lidya Angelyna Putri Kadir; Refa M. Tancepa; Nazwa Azizia Lukum; Isniarty Gintulangi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to analyze the contribution of emotion regulation and resilience to Non-Suicidal Self-Injury (NSSI) as a form of psychopathology in adolescents. The research method used is a literature review of 26 scientific articles published between 2019 and 2025. The findings indicate that emotion dysregulation and high self-criticism are major predictors of self-harming behavior, often used as a maladaptive coping strategy to manage emotional distress. Adolescents with poor emotional control are more vulnerable to engaging in NSSI. In contrast, resilience acts as an important protective factor that helps reduce the tendency toward self-injury through the development of adaptive coping, social support, and self-compassion. Strengthening resilience enables adolescents to better manage stress and negative emotions. The study concludes that psychological interventions focusing on improving emotion regulation and resilience are essential to reduce the risk of psychopathology and promote better mental health among adolescents.